Pengaruh Tingkat Pendidikan Orang Tua dan Pemanfaatan Handphone Terhadap Hasil Belajar Siswa Kelas IV SD Negeri 064017 Medan Perjuangan - Sufitriyati, Sufitriyati; Ananda, Lala Jelita; Simbolon, Naeklan; Manurung, Imelda Free Unita; Simanihuruk, Lidia (Journal of Computer Science and Information System(JCoInS), 2023)
The aim of the research is to describe the influence of parental education level and use of cellphones on the learning outcomes of class IV students at SD Negeri 064017 Medan Perjuangan. This research is qualitative research with a descriptive approach. The samples for this research were parents and fourth grade students at SD Negeri 064017 Medan Perjuangan. The data collection techniques used were interviews, questionnaires and documentation. This research uses a flow model qualitative research data analysis cycle which consists of three stages, namely data reduction, data presentation, and drawing conclusions. The results of the research show that the last education of parents who were S1 (Strata-1) was 1 person with a percentage of 4%, the last education of parents who were high school/equivalent was 19 people with a percentage of 79%, the last education of parents who were junior high school/equivalent was 3 people. with a percentage of 13% and the parent's last education was elementary school, amounting to 1 person with a percentage of 4%. This shows that the final education of the parents of class IV students at SD Negeri 064017 Medan Perjuangan is more than SMA/SMK/MA graduates. Parents' latest education influences the learning outcomes of class IV students at SD Negeri 064017 Medan Perjuangan. The results showed that the learning outcomes of class IV students at SD Negeri 064017 Medan Perjuangan were in the low category as many as 12 people with an average of 50%, the learning outcomes of students in the medium category were 5 people with an average of 21%, the students' learning outcomes were in the There were 2 people in the sufficient category with an average of 8%, and there were 5 students in the high category with an average of 21%. From the data obtained, there were 87.5% of parents with details of the final education of the parents of 17 high school/vocational school graduates, 1 elementary school student and 3 high school students who stated that the use of cellphones had a negative influence on their children, such as being lazy about studying, late eating at home, lying to friends via social media and seeing bad things on social media. This shows that the negative influence of cellphones is greater than the positive influence of cellphones if there is no supervision and guidance from each parent.